Joseph Banks and Charles Blagden: cultures of advancement in the scientific worlds of late eighteenth-century London and Paris. (20th February 2019) - Wills, Hannah
Abstract : This paper explores the relationship between Joseph Banks, president of the Royal Society, and Charles Blagden, secretary to Banks and the Society between 1784 and 1797. Blagden is often referred to as one of Banks's key assistants, as a trusted adviser, collaborator and source of information. Yet, despite his significance, the nature of Blagden's association with Banks has not been explored in detail. This paper traces the development of their sometimes tumultuous relationship, exposing it as one in which Blagden, an aspiring gentleman, sought Banks's patronage to further his career and social ambitions. Key to Blagden's strategy was his role as a source of information for Banks from Paris. Yet, while Blagden pursued patronage with Banks in London, on visits to Paris he encountered a situation where merit, in terms of published scientific outputs, determined one's membership of the scientific community. Exploration of these conflicting cultures of advancement—patronage versus advancement through merit—here informs a re-assessment of scientific exchange at a key moment in Blagden's career, the 1783 'water controversy'. The limitations of Banks's patronage for ambitious clients are also explored, in the context of a rupture in the relationship between Blagden and Banks at the end of the 1780s.